FENOMENA MUSIK KAFE PADA COFFEECCINO CAFÉ DI KOTA PONTIANAK - Ridho i, Amy Manap (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to find out Fenomoena music cafe in Pontianak city especially at Coffeeccino Café. The method used is descriptive method, qualitative research form, and case study. Data collection techniques are observation, direct communication, and documentation. Data analysis using case study method with attention to four indicators of interest to the cafe that is the level of education, age, and entertainment-seeking factors. Based on the level of education are students. Based on the age of 17 years and over. Based on the income level, it does not matter because the price is set standard. Based on the entertainment-seeking factor, the whole involved to find entertainment. Another problem is the driving and inhibiting factors. For the driving factor is more dominant than the inhibiting factor. Unruk education, students are more likely to be encouraged to enjoy the cafe music. Based on age, there are no obstacles because there is no regulation to regulate the age limit. Based on the income level, there are no significant obstacles. Based on the factor of finding entertainment there are no obstacles. Â Keywords: Music, Cafe, Case Study.